Pielonefrite Cronica: una Causa Misconosciuta di Perdita del Trapianto di Rene - Valeria Corradetti; Eleonora Pattonieri; Chiara Rocca; Teresa Valsania; Marilena Gregorini; Teresa Rampino; Claudia Martinelli; Pasquale Esposito; Antonio Dal Canton (AboutScience Srl, 2015)
Abstract non disponibile